Correlation between non-exclusive breastfeeding and low birth weight to stunting in children - Endang Dewi Lestari; Faraissa Hasanah; Novianti Adi Nugroho (Indonesian Pediatric Society, 2018)
Background Indonesia is ranked fifth in the world for the problem of stunting. Stunting in children under the age of five requires special attention, due to its inhibiting effect on children’s physical and mental development. Stunting is caused by several factors, one of which is breastfeeding. Stunting has been associated with several factors, one of which is non-exclusive breastfeeding. Objective To determine the correlations between non-exclusive breastfeeding and low birth weight to stunting in children aged 2-5 years. Methods This case-control study was conducted in October to November 2016 in multiple integrated health service clinics (posyandu) in Sangkrah, Surakarta, Central Java, Indonesia. Subjects were children aged 24-59 months who visited the posyandu and were included by purposive sampling. Children classified as stunted were allocated to the case group, whereas the children classified with normal nutritional status were allocated to the control group. Parents filled questionnaires on history of exclusive breastfeeding, child’s birth weight, maternal education, and family socio-economic status. Results Of the 60 subjects, the control group had 30 normal children and the case group had 30 stunted children. Multivariate analysis by logistical regression test revealed statistically significant correlations between stunting and non-exclusive breastfeeding (adjusted OR for exclusive breastfeeding 0.234; 95%CI 0.061 to 0.894), as well as low birth weight (adjusted OR 10.510; 95%CI 1.180 to 93.572) This value implies that exclusive breastfeeding is a protecting factor against stunting, which means exclusive breastfeeding is able to decrease the prevalence of stunting in children under the age of five. Conclusion In children aged 2-5 years, the histories of non-exclusive breastfeeding and low birth weights are significantly correlated sith stunting.